2012
DOI: 10.1146/annurev-nutr-071811-150646
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Intervention Strategies and Examples for Obesity Prevention in Children

Abstract: With obesity affecting approximately 12.5 million American youth, population-level interventions are indicated to help support healthy behaviors. The purpose of this review is to provide a summary of population-level intervention strategies and specific intervention examples that illustrate ways to help prevent and control obesity in children through improving nutrition and physical activity behaviors. Information is summarized within the settings where children live, learn, and play (early care and education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 76 publications
0
64
0
4
Order By: Relevance
“…Primary care providers 7,8 and family pediatricians, in particular, may be an effective point of contact for early prevention, but their involvement is not so obvious. In fact, screening and tracking BMI percentile according to age and encouraging healthy nutrition and physical activity (PA) are recommended but are not universally delivered in pediatric care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary care providers 7,8 and family pediatricians, in particular, may be an effective point of contact for early prevention, but their involvement is not so obvious. In fact, screening and tracking BMI percentile according to age and encouraging healthy nutrition and physical activity (PA) are recommended but are not universally delivered in pediatric care.…”
mentioning
confidence: 99%
“…9,13 Systematic reviews have found strong evidence that childhood obesity prevention programs can reduce BMI, particularly those programs targeting children aged 6 to 12 years compared with those targeting teenagers. 14 They have also shown that a behavioral approach to changing lifestyle in children 15 or multisetting strategies 7 can produce significant and clinically meaningful weight reduction in children compared with standard care or self-help. 16 Some studies also highlight the need to pay attention to parental influence, 17 especially for younger children, 18 as parents are sometimes unconcerned about their child' s weight status 19 and they may not believe that excess weight gain can negatively affect their child' s health.…”
mentioning
confidence: 99%
“…Successful approaches need to target multiple sectors and levels of influence simultaneously, [8][9][10][11] as indicated by the whole-child approach, 12 ''Total Worker Health,'' 13 the Social Ecological Framework (SEF), 14,15 and several reviews and commentaries. [16][17][18][19][20][21] According to SEF, including its application to US Latinos, 22,23 levels of influence range from most to least proximal to the individual (see Fig.…”
Section: Preventing and Controlling Childhood Obesitymentioning
confidence: 99%
“…The CA-CORD intervention is based on the study team's previous research, 29,[31][32][33][34][35][36] several systematic reviews, [8][9][10]21,[37][38][39][40][41] CA-CORD CAC input, and formative research. CA-CORD CAC members were identified during the grant-writing phase by responding to a request for participation in a community-wide approach to prevent and control childhood obesity.…”
Section: Development Of the Ca-cord Intervention Approachmentioning
confidence: 99%
“…This has important implications for researchers and policy makers. Early-care education has also been identified as a recommended framework for conducting an intervention for young children (23) . However, there exists a gap in research to determine effective interventions in young children (24) .…”
mentioning
confidence: 99%